Conflict and Transnational Crime: Borders, Bullets & Business in Southeast Asia - Florian Weigand (Edward Elgar Publishing, 2020)
Exploring the links between armed conflict and transnational crime, Florian Weigand builds on in-depth empirical research into some of Southeast Asia$1 (Bs murkiest borders. The disparate voices of drug traffickers, rebel fighters, government officials and victims of armed conflict are heard in Conflict and Transnational Crime, exploring perspectives that have been previously disregarded in understanding the field.s
English
Keywords: insurgency; Armed conflict; borders; rebels; smuggling; transnational crime book